Characterizing Hyperbolic Functions over a Hyperplane - PONPETCH, Kanet (Walailak Journal of Science and Technology (WJST), 2019)
A brief account of our recent works dealing with the problem of characterizing hyperbolic functions through the use of functional equations with side conditions is reported. Specifically, the fact that each of the n functions having a zero sum over n points lying in a hyperplane is necessarily a linear function, is generalized and the results so obtained are applied to characterize hyperbolic functions.